Pediatric non-Hodgkin lymphoma: Characteristics, stratification, and treatment at a single institute in Thailand - Worawut Choeyprasert (2019)
© 2018 Japan Pediatric Society Background: In the modern era of chemotherapy, the outcome of pediatric non-Hodgkin lymphoma (NHL) continues to improve internationally. Limited data such as information on epidemiology and survival, however, are available in Asian countries. Methods: Children (≤15 years old) diagnosed with histologically proven NHL from 1998 to 2014 were retrospectively analyzed. Results: In total, 114 patients were enrolled; they were predominantly male (65.8%) and had advanced disease (stage III, IV; 71.9%). Of these, 22.8% had Burkitt lymphoma, 20.2% had diffuse large B-cell lymphoma, 21.1% had lymphoblastic lymphoma, 20.2% had large cell lymphoma, and 15.8% had peripheral T-cell lymphoma. Twenty-nine patients died, especially of uncontrolled disease (62.1%) and infection (20.7%). During a median follow up of 78.4 months, Kaplan–Meier 5 year event-free and overall survival rates were 71.5% ± 4.3% and 74.8% ± 4.1%, respectively, regardless of subtype. B symptoms (i.e. systemic symptoms of fever, night sweats, and weight loss that can be associated with both Hodgkin's lymphoma and non-Hodgkin's lymphoma) and advanced disease had a significant negative impact on 5 year survival. No other prognostic factor was found, but survival tended to have a negative correlation with age. Conclusions: Pediatric NHL is aggressive, with a high prevalence of peripheral T-cell lymphoma. The present treatment stratification seems to be effective compared with that used in developed countries.